The first lower hybrid current drive experiments in the spherical tokamak Globus-M. (4th September 2015) - Dyachenko, V.V.; Shcherbinin, O.N.; Gusakov, E.Z.; Gusev, V.K.; Irzak, M.A.; Kurskiev, G.S.; Petrov, Yu.V.; Saveliev, A.N.; Sakharov, N.V.; Khitrov, S.A.; Khromov, N.A.; Varfolomeev, V.I.; et al.
Abstract: First experiments on non-inductive current drive (CD) in the spherical tokamak using lower hybrid (LH) waves at 2.45 GHz are described. The basic characteristics of the new experimental approach utilizing poloidal LH wave slowing-down scheme obtained by modeling are presented at the beginning of the paper. The experimental results for a poloidal slowing-down scheme are described. The CD efficiency comparable or even higher than theoretically predicted is demonstrated in the experiment using a 10 waveguide grill with 120° phase shift between neighboring waveguides.